High flow nasal cannula oxygen therapy versus bilevel positive airway pressure as a mode of oxygen delivery a prospective observational study in patients with pneumonia and hypoxemic respiratory failure - Aniket Ashok Satale,; Nutan Agarwal,; Mohd Zaki Siddique,; Gaurav Singh,; Neha Rathore, (Asian Journal of Medical Sciences, 2025)
Background: High-flow nasal cannula (HFNC) and bilevel positive airway pressure (BiPAP) are common non-invasive ventilation strategies, but their comparative effectiveness in oxygenation and patient outcomes remains under investigation. Aims and Objectives: This study compares the efficacy of HFNC and BiPAP in patients with pneumonia and hypoxemic respiratory failure (HRF). Materials and Methods: Patients with pneumonia and HRF admitted to the intensive care unit or emergency department were assigned to either HFNC or BiPAP based on clinical judgment. Outcomes assessed included oxygenation (PaO2/FiO2), respiratory rate, patient comfort, intubation rates, hospital stay length, and survival. Results: HFNC and BiPAP showed similar short-term oxygenation improvements. HFNC provided better comfort and ease of use, while BiPAP offered superior ventilation support and respiratory rate reduction. Both methods had comparable intubation rates and hospital stay lengths, though BiPAP may benefit patients with severe distress. Conclusion: HFNC improved oxygenation and shortened hospital stays, while BiPAP enhanced ventilation. Mortality rates were similar, suggesting both can be used in managing mild acute respiratory distress syndrome, depending on patient needs and available resources.